Analisis Kesulitan Mahasiswa Dalam MenyelesaikanPersamaan Differensial Tingkat Satu - Oktavia, Ayu (2016)
The purpose of research to analyze the types of difficulties and the factors that cause difficulty in solving differential equations orde one. This research qualitative descriptive. The subjects were master students of fifth grade Mathematic Education FKIP UMS total 7 people. Data collection methods interviews and documentation. Data analysis techniques through data reduction, data display, and conclusion. The results showed master students having difficulty, The first difficulty understanding the concept of which is divided into two: (1) the difficulty formulating a common characteristic or shape differential equation; (2) the difficulty determining completion techniques differential equation. Two, the difficulty of applying the concept which is divided into two: (1) the difficulty in calculation steps; (2) Difficulties in the material prerequisites. Factors that cause master students to experience difficulties, first intrinsic factors, namely: the learning activities, difficulties remembering the formula, bad habits, lack of exercise, lack of motivation to learn, educational background that is not appropriate. Both extrinsic factors, that are active in social activities in the neighborhood.